2010
DOI: 10.1093/eurjhf/hfq092
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Connexin43 distribution in heart failure is associated with dispersed conduction and enhanced susceptibility to ventricular arrhythmias

Abstract: AimsSudden arrhythmogenic cardiac death is a major cause of mortality in patients with congestive heart failure (CHF). To investigate determinants of the increased arrhythmogenic susceptibility, we studied cardiac remodelling and arrhythmogenicity in CHF patients and in a mouse model of chronic pressure overload. Methods and resultsClinical and (immuno)histological data of myocardial biopsies from CHF patients with (VT+) and without (VT2) documented ventricular arrhythmia were compared with controls. In CHF pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 32 publications
3
63
2
Order By: Relevance
“…It seems that cardiac insufficiency consists of 2 components, the sequence of contraction on one hand and the cellular biochemical alterations on the other hand, which finally lead to progressive pathological remodeling. 25 Compared with other studies carried out on animal models of cardiac failure and on explanted hearts of patients with terminal heart failure that revealed a decrease in L-type calcium and peak sodium currents, a prolongation of action potential, a decrease in SERCA and phospholamban, an increase in catecholamine levels, and a heterogeneous distribution of Cx43, [31][32][33][34][35] our results are different in terms of the expression of the calcium handling proteins and Cx43 distribution. However, as outlined above, our paced minipigs were cardiac compensated, and it is conceivable that ultrastructural remodeling is much more pronounced in overt heart failure, as seen in tachycardia pacing studies performed on dogs.…”
Section: Preservation Of LV Function With Lv Apex Pacingcontrasting
confidence: 81%
“…It seems that cardiac insufficiency consists of 2 components, the sequence of contraction on one hand and the cellular biochemical alterations on the other hand, which finally lead to progressive pathological remodeling. 25 Compared with other studies carried out on animal models of cardiac failure and on explanted hearts of patients with terminal heart failure that revealed a decrease in L-type calcium and peak sodium currents, a prolongation of action potential, a decrease in SERCA and phospholamban, an increase in catecholamine levels, and a heterogeneous distribution of Cx43, [31][32][33][34][35] our results are different in terms of the expression of the calcium handling proteins and Cx43 distribution. However, as outlined above, our paced minipigs were cardiac compensated, and it is conceivable that ultrastructural remodeling is much more pronounced in overt heart failure, as seen in tachycardia pacing studies performed on dogs.…”
Section: Preservation Of LV Function With Lv Apex Pacingcontrasting
confidence: 81%
“…16 Spatial heterogeneity in Cx43 expression in our study was quantified (as described before) 17 and showed a significantly higher heterogeneous Cx43 expression in TAC operated compared with sham-operated mice. Areas almost deprived of Cx43 protein neighboured areas with normal Cx43 expression.…”
Section: N T E R U N I V E R S I T Y C a R D I O L O G Y I N S T I mentioning
confidence: 63%
“…15,19,27 Interestingly, we showed that this increase in fibrosis is more prominent in Cx43 Cre-ER(T)/fl compared with Cx43 fl/fl hearts. As a possible mechanism for the enhanced fibrosis in stressed hearts with reduced Cx43 levels, we hypothesized that reduced Cx43 levels may alter cardiomyocyte/fibroblast and fibroblast/fibroblast communication, leading to increased fibroblast proliferation and/or activity.…”
Section: Fibroblast Proliferation and Activitymentioning
confidence: 71%
“…19 A gradient of Ϸ50% was confirmed by Doppler echocardiography. Sham-operated Cx43 fl/fl (nϭ12) and Cx43 Cre-ER(T)/fl (nϭ10) mice were used as control.…”
Section: Animalsmentioning
confidence: 87%